Framing holes within a loop hierarchy. Issue 1 (2nd January 2016) - Santos, Paulo E.; Cabalar, Pedro
Abstract : We investigate the relation between nontrivial spatial concepts such as holes and string loops from a qualitative spatial reasoning perspective. In particular, we concentrate on a family of puzzles dealing with this kind of objects and explain how a loop formed in a string shows a similar behavior to a hole in an object, at least regarding the qualitative constraints it imposes on the solution of the puzzle. Unlike regular holes, however, we describe how string loops can be dynamically created and destroyed depending on the actions on the string. Furthermore, under a Knowledge Representation point of view, we provide a formalization that allows the different puzzle states to be described in terms of string crossings and loops, together with the actions that can be executed for a state transition and the complex effects they cause on the state representation. This implies the consideration of a formal representation of the side effects of actions that create or destroy string loops and the soundness of this representation with respect to the more general representation of string states in knot theory.